1986
DOI: 10.1080/00207238608710257
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of fly ash—an environmental problem

Abstract: This report intends to summarize impacts of fly-ash disposal on soil-water environment with special reference to the behaviour of trace elements. Physico-chemical properties of fly-ash and trace elements release in environment are dependent on the geological origin of coal, form of the element in coal, combustion products, type of coal burning process, nature of emission control devices, methods of disposal and climatic conditions. Physical and biological transport of trace element, their bioaccumulation, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 50 publications
0
24
0
1
Order By: Relevance
“…Because of the presence of Ca-Si minerals with a pozzolanic nature (zeolite formation), along with the moisture of the soil (Fulekar and Dave, 1986), fly ash brings about improvements in various physico-chemical properties, such as BD, porosity, WHC, and the available water in the soil. In particular, the fly ash has a higher silt content than soil, and the infiltration rate of sandy soils or mine spoil is drastically checked because of the increase in silt (Furr et al, 1977), whereas in the clay-rich type of soils, the reverse is the case, with better water movement and workability, apart from decreased plasticity or crack formation after drying.…”
Section: Plausible Mechanism For Improvement Of Soil Healthmentioning
confidence: 99%
“…Because of the presence of Ca-Si minerals with a pozzolanic nature (zeolite formation), along with the moisture of the soil (Fulekar and Dave, 1986), fly ash brings about improvements in various physico-chemical properties, such as BD, porosity, WHC, and the available water in the soil. In particular, the fly ash has a higher silt content than soil, and the infiltration rate of sandy soils or mine spoil is drastically checked because of the increase in silt (Furr et al, 1977), whereas in the clay-rich type of soils, the reverse is the case, with better water movement and workability, apart from decreased plasticity or crack formation after drying.…”
Section: Plausible Mechanism For Improvement Of Soil Healthmentioning
confidence: 99%
“…Elevated selenium levels measured in aquatic specimens from the Labin City area (Miko et al, 2003), together with the results in Table 3, provide an evidence for the potential leaking of coal ash deposits around the PPP, what should be investigated by future more detailed studies. Such studies are necessary as Fulekar and Dave (1986) reported that Se was found among the elements extracted either by water or acid, and particularly in effluent waters related to disposed coal ash by-products. Furthermore, the authors point out that Cd and Pb were found by previous studies to be correlated with human health problems due to coal combustion.…”
Section: Aquatic and Herbal Geochemistrymentioning
confidence: 99%
“…Although the sulphur content in coal varies considerably, its total levels most commonly range from 0.50% to 5.00% (Rađenović, 2004;Chou, 2012). Fulekar and Dave (1986) reported that the total S content in major Indian coals (except those of Assam, Jammu and Kashmir which contain S up to 14.0%, and are not used in power plants) are between 0.20% and 1.40%. Superhigh-organic-sulphur (SHOS) coal is a special class of coal, characterised by remarkably elevated values of organic S, usually in the range of 4.00-11.0%.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide huge amounts of CFA are generated in order to meet energy demands, and about 70% of CFA is disposed as waste [1]. CFA disposal is of great concern globally due to the environmental issues arising from the disposal methods that are currently employed [2][3][4]. CFA is considered a highly contaminating medium because the toxic trace elements in coal are accumulated in higher concentrations in the combustion by product [5].…”
Section: Introductionmentioning
confidence: 99%